Assessment of Ecological Environment in Zhanjiang Based on RSEI and PCA - Cheng, Xiaoyuan; Wang, Ruei-Yuan; Liu, Haolong; Wang, Yun-Shang (International Journal of Environment, Agriculture and Biotechnology, 2023)
This study uses Landsat-8 remote sensing images as the data source and selects four indicators that directly reflect the quality of the ecological environment, such as greenness (NDVI), wetness (WET), dryness (NDBSI), and heat (LST). Meanwhile, we use principal component analysis (PCA) to construct a remote sensing ecological index (RSEI) model for exploring the changes in the ecological environment quality of Zhanjiang from 2013 to 2021. The results indicate that RSEI can better reflect the ecological environment of the region. The study area is mainly affected by dryness, followed by greenness and humidity, with heat having the smallest impact. The average RSEI values in Zhanjiang City in 2013 and 2021 were 0.5339 and 0.5576, respectively, indicating a slight improvement in overall ecological environment quality. Among them, NVDI showed an increasing trend, NDBSI and WET decreased, but LST increased.